Error Correction Mechanism (ECM) Analysis for Identifying Factors that Influence Tax Income in Indonesia - Sugiarto -; Merisa Widyasari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2016)
The under necessity of taxpayer number and the low of tax ratio in Indonesia indicate about small tax base revenue. it is contrary to the large population size that should have great potential against the tax. Theoritically, the tax revenue in the country are affected by various factors including Foreign Direct Investment (FDI), Gross Domestic Product (GDP), exports, and imports. This study aimed to analyze the influence of foreign investment (PMA), Gross Domestic Product (GDP), exports and imports to tax revenues in Indonesia in the long term and short term. The analytical method used in this study is Error Correction Mechanism (ECM) with study period 1984-2013. The study results show that in the long term, FDI, export, and import have significant positive impact on tax revenues, while the GDP has no significant positive effect on tax revenue. In the short term, FDI, GDP, export, and import have significant positive impact on tax revenue in Indonesia. The study result can be imply to the imports selection, improving the quality of exported goods and facilitate administration services of investment is the main point to increase tax revenues.